Assessment of the relationship between selected factors and stress-coping strategies in handcyclists - A preliminary study - Turon-Skrzypinska, A.; Pawlukowska, W.; Szylinska, A.; Tomska, N.; Mikolajczyk-Kociecka, A.; Ptak, M.; Dutkiewicz, G.; Rotter, I. (Medicina, 2020)
Background and Objectives: Playing competitive sports is associated with stress, especially during the starting season. Disabled athletes are additionally burdened with physical and/or emotional factors, resulting from the trauma they have experienced. The aim of the work was to assess the relationship between strategies of coping with stress and the level of education, category of disability and its duration of handcyclists before the competition. Materials and Methods: 44 handcyclists with a mean age of 41.8 ± 11.6, from European countries, were divided according to the severity of mobility impairments, education and duration of the disability. The participants were asked to fill in the Mini-COPE Inventory for Measuring Coping with Stress, which provided answers in writing to some sociodemographic questions regarding age, sex, education, type of mobility impairment and duration of the disability. Results: The subjects who had suffered spinal injury at the cervical section obtained the lowest scores regarding their subjective assessment of their active stress management in difficult situations (p = 0.007). They scored the lowest, 1.5 points, when asked about acceptance in difficult circumstances compared to those with university education (p = 0.02). A statistically significant correlation was found to exist between education levels and positive revaluation, acceptance and seeking instrumental support. A negative correlation was observed between education and sustained use of psychoactive substances and denial. Conclusions: Highly educated cyclists with short-lasting disability, damage to the lower spine section or amputations tend to cope better with stress than other study participants.